Driving heat [compact disc, unabridged] - Castle, Richard (Hachette Audio, 2015)
The NYPD's top homicide detective Nikki Heat has been promoted to captain just in time to face a case with a very personal twist. Captain Heat's fiancé, reporter Jameson Rook, is deep in an investigation. Professionally for Heat, Rook's meddling compromises her new job. Privately, it becomes an early test of their engagement as their parallel lives not only cross, but collide.